How we met [videorecording (DVD)] - Hopson, Chadwick; Hopson, Chadwick; Flaccus, Brian; Lozoya, Oscar Rene, II; Moses, Christina (Christina Marie), 1978-; Ice-T (Musician) (BayView Entertainment, 2022)
A sheltered young loser goes on the worst blind date ever when he and his date must cover up the accidental murder of a crooked cop.